Taking an Idea from Inception to Innovation: Evolution in Restrictive Transfusion Criteria - Wax, Mark K. (Facial Plastic Surgery, 2020)
Innovation in surgical care is a complex procedure. When you reflect on how your practice has changed, whether it be 5 years or over decades, it can be enlightening to not only see the change but also conceptualize how it came about. Examining one's practice as part of Pittsburgh Sleep Quality Index or as a result of reading the literature, attending a meeting, or some other educational activity can lead one to question if there is a better method available. In this manuscript, I will describe how outside influences initiated a paradigm shift that ultimately benefited patient care, the system, and my practice. The methodology has been used over the course of my career to influence and modulate practice patterns.
Keywords: transfusion; free flap; hematocrit; head and neck